1901 Texas Spec. Laws 74: §§ 169-170. - (:unkn) unknown (My University, 1901)
The city council may also regulate or prohibit and prevent the carrying on of work and manufactures that are dangerous in promoting or causing fires, and may prohibit the building or erection of cotton presses and sheds, or may restrict the same to such limits as are prescribed by ordinance; and may regulate or prohibit and prevent the use of fireworks and firearms, or the keeping and management of houses or other structures or places for storing gunpowder, dynamite, or other combustible, explosive, or dangerous material or substances within the city, and may regulate the keeping and conveying of the same.
Keywords: DISCHARGE; GUNPOWDER - STORAGE